Restitusi Sebagai Upaya Ganti Kerugian atas Derita yang Dialami Anak Akibat Pencabulan yang Dilakukan Oknum Guru di Lingkungan Sekolah - Suryani, Dewi Ervina (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2023)
Initially, restitution was more popular in the field of civil law, but along with the development of criminal law, the term restitution was heard more often, especially in criminal cases involving children as victims. Child victims have the right to obtain compensation for the suffering they experience as a result of criminal acts. However, the implementation of this restitution cannot yet be said to be optimal, because there are still many children who are victims of criminal acts, especially sexual abuse, who do not receive restitution as they should, and some even do not know about it. This research is normative juridical by examining secondary data (library research). The results of this research provide an illustration of how the fulfillment of children's rights and protection is implemented in the decision of the Banda Aceh District Court in case Number: 132/Pid.Sus/2020/PN Bna, which is a case of sexual abuse committed by unscrupulous teachers at SD Negeri 64 Banda Aceh Ateuk Jawo Village , Baiturrahman District, Banda Aceh City to underage female students.